Os impactos da territorialização dos assentamentos rurais em Candiota - RS - Alves, Flamarion Dutra (2006)
This study analyzes the impacts of rural settlements territorialization in the Candiota County, located in the south region of the Rio Grande do Sul. The topic starts from the territorial occupation of Rio Grande do Sul state that begins with regional differences, one side the great property in the south region and another one, the small property in north-northeast region of the state. The modernization process in agriculture, from 1960, amplifies the socialeconomical difference causing the increase of the rural exodus, land and income concentration. Consequently, begins social movements in the rural areas, which demanded land distribution and agrarian structure modification. In the end of the decade of 1980, it establishes rural settlements in Candiota causing a reduction in the agrarian concentration and increasing the social-economical dynamism in the rural area of the County. In 2006, Candiota has twenty and five rural settlements with 693 families. They had modified and generate a new dynamics in the County.